Development and cytological characterization of wheat–Thinopyrum intermedium translocation lines with novel stripe rust resistance gene - Guo, Xianrui; Huang, Yuhong; Wang, Jing; Fu, Shulan; Wang, Chunhui; Wang, Mian; Zhou, Chen; Hu, Xiaojun; Wang, Tao; Yang, Wuyun; Han, Fangpu (Frontiers in Plant Science, 2023)
Wheat stripe rust is a destructive disease in many cool and temperate regions around the world. Exploiting novel sources of resistance can provide wheat cultivars with robust and durable resistance to stripe rust. The wheat-Thinopyrum intermedium addition line TAI-14 was proven to carry a stripe rust resistance gene (named as YrT14) on the alien Th. intermedium chromosome. In order to transfer the resistance gene to wheat, wheat-Th. intermedium translocation lines were created by irradiating the pollen of the line TAI-14. We totally obtained 153 wheat-Th. intermedium translocation lines, among which the long alien segmental translocation line Zhongke 78 and the intercalary translocation line Zhongke 15 not only showed good integrated agronomic traits but also were identified as highly resistant to stripe rust in both seedling and adult plant stages. The alien chromatin in Zhongke 15 was identified as an insertion into the satellite of chromosome 6B, a type of translocation never reported before in chromosome engineering. By screening SSR and EST markers as well as the markers developed from RNA-Seq data, fourteen markers were identified specific for the alien chromosome and a physical map was constructed. Both Zhongke 78 and Zhongke 15 could be used as a novel source of stripe rust resistance for wheat breeding, and the linked marker T14K50 can be used for molecular marker-assisted breeding. Finally, based on the karyotype, reaction to stripe rust and genome resequencing data of different wheat-Th. intermedium translocation lines, the stripe rust resistance gene YrT14 was located to an 88.1 Mb interval from 636.7 to 724.8 Mb on Th. intermedium chromosome 19 corresponding to 7J or 7Js.